CDCP1 overexpression drives prostate cancer progression and can be targeted in vivo. - Alajati, A.; D'Ambrosio, M.; Troiani, M.; Mosole, S.; Pellegrini, L.; Chen, J.; Revandkar, A.; Bolis, M.; Theurillat, J.P.; Guccini, I.; Losa, M.; Calcinotto, A.; et al. (Journal of Clinical Investigation, 2020)
The mechanisms by which prostate cancer shifts from an indolent castration-sensitive phenotype to lethal castration-resistant prostate cancer (CRPC) are poorly understood. Identification of clinically relevant genetic alterations leading to CRPC may reveal potential vulnerabilities for cancer therapy. Here we find that CUB domain-containing protein 1 (CDCP1), a transmembrane protein that acts as a substrate for SRC family kinases (SFKs), is overexpressed in a subset of CRPC. Notably, CDCP1 cooperates with the loss of the tumor suppressor gene PTEN to promote the emergence of metastatic prostate cancer. Mechanistically, we find that androgens suppress CDCP1 expression and that androgen deprivation in combination with loss of PTEN promotes the upregulation of CDCP1 and the subsequent activation of the SRC/MAPK pathway. Moreover, we demonstrate that anti-CDCP1 immunoliposomes (anti-CDCP1 ILs) loaded with chemotherapy suppress prostate cancer growth when administered in combination with enzalutamide. Thus, our study identifies CDCP1 as a powerful driver of prostate cancer progression and uncovers different potential therapeutic strategies for the treatment of metastatic prostate tumors.